2015
DOI: 10.3390/rs71012635
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-2 for Mapping Iron Absorption Feature Parameters

Abstract: Iron is an indicator for soil fertility and the usability of an area for cultivating crops. Remote sensing is the only suitable tool for surveying large areas at a high temporal and spatial interval, yet a relative high spectral resolution is needed for mapping iron contents with reflectance data. Sentinel-2 has several bands that cover the 0.9 µm iron absorption feature, while space-borne sensors traditionally used for geologic remote sensing, like ASTER and Landsat, had only one band in this feature. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 39 publications
3
39
0
2
Order By: Relevance
“…They concluded that sensors like Sentinel-2A MSI are suitable for detection of Gossan with their method, and that they potentially can save costs when used for target detection prior to hyperspectral data acquisition. Van der Werff and van der Meer [23] demonstrated the capabilities of Sentinel-2A MSI for geological remote sensing by mapping iron oxide mineralogy. This was done by introducing a modelling approach on the 0.9 µm iron absorption feature using Sentinel-2A MSI's near-infrared (NIR) bands 6-9.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that sensors like Sentinel-2A MSI are suitable for detection of Gossan with their method, and that they potentially can save costs when used for target detection prior to hyperspectral data acquisition. Van der Werff and van der Meer [23] demonstrated the capabilities of Sentinel-2A MSI for geological remote sensing by mapping iron oxide mineralogy. This was done by introducing a modelling approach on the 0.9 µm iron absorption feature using Sentinel-2A MSI's near-infrared (NIR) bands 6-9.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low spectral resolution of ASTER VNIR data (only three bands), it is difficult to identify the iron oxides such as goethite, jarosite, and haematite. The recently launched spaceborne systems such as Tiangong-1 Hyperspectral Imager (HSI) and Sentinel-2 and the upcoming GF-5 HSI and EnMAP could no doubt provide new opportunities supporting mineral exploration, especially for the VNIR spectral range (Liu, Feng et al, 2017;Rogge, Rivard, Segl, Grant, & Feng, 2014;van der Werff & van der Meer, 2015). Specially, the Sentinel-2 has 10 bands in the VNIR and 3 bands in the SWIR wavelength region, and the spatial resolution of these bands differs between 10, 20, or 60 m with a 290 km swath width (van der Werff & van der Meer, Werff & van der Meer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Satellite missions, labelled Sentinel 1 up to 5, were set up for environmental monitoring [63]. The launch of Sentinel-2 in 2015 opened a new era in remote sensing.…”
Section: Satellitementioning
confidence: 99%
“…Van der Werff and van der Meer [63] summarized spectral position (λ) and bandwidth (∆λ), spatial resolution, heritage and purpose of Sentinel-2 bands, according to the Copernicus derived user requirements.…”
Section: Satellitementioning
confidence: 99%